Synthesis, structural, magnetic and thermal studies of copper(II) 5, 5-diethylbarbiturate complexes with nicotinamide, 2, 2′-bipyridine and triethanolamine. Issue 3 (16th February 2023) - Yilmaz, Veysel T.; Yilmaz, Fatih; Icsel, Ceyda; Aygun, Muhittin
Abstract: Three new copper(II) 5, 5-diethylbarbiturate (barb) complexes of nicotinamide (nia), 2, 2′-bipyridine (bpy) and triethanolamine (tea), trans -[Cu(barb)2 (nia)2 ]⋅2H2 O (1 ), cis -[Cu(barb)2 (bpy)]⋅3H2 O (2 ) and [Cu2 (barb)2 (tea)2 ]⋅2H2 O (3 ), were synthesized and characterized by elemental analysis, spectroscopic (UV-Vis and FTIR) and magnetic moment measurements. Single crystal X-ray crystallographic measurements showed that 1 and 2 are mononuclear, while 3 is binuclear, in which two copper centers were bridged by deprotonated ethanol groups of two tea ligands. The barb ligand in these complexes is a bidentate N, O-donor. Thermal analysis (TG/DTA) studies in air indicated that the complexes first dehydrated and then the decomposition of nia, bpy or tea ligands occurred. The last exothermic stage was associated with degradation of the barb moiety to yield CuO as the end product. Abstract : UF0001